1996
DOI: 10.1128/jcm.34.1.130-133.1996
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gen-Probe Amplified Mycobacterium Tuberculosis Direct Test and Roche PCR-microwell plate hybridization method (AMPLICOR MYCOBACTERIUM) for direct detection of mycobacteria

Abstract: We evaluated the clinical utility of an rRNA amplification-based Gen-Probe Amplified Mycobacterium Tuberculosis Direct Test (AMTD) system and a PCR-based Roche AMPLICOR MYCOBACTERIUM system for direct detection of Mycobacterium tuberculosis, M. avium, and M. intracellulare. Of the 422 sputum samples from 170 patients, 137 (121 of M. tuberculosis, 14 of M. avium-M. intracellulare complex [MAC], 2 of mycobacterium other than M. tuberculosis or MAC) were culture positive with the Septi-Chek AFB system. One sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 31 publications
2
13
0
1
Order By: Relevance
“…The high sensitivity (94%) and specificity (100%) are similar to results reported in other studies. Ichiyama et al reported 97% sensitivity and 98.7% specificity, however Vuorinen et al reported slightly lower sensitivity of 84.6% and specificity of 99.1% using similar commercially available PCR (Amplicor) with IS6110 as a target site for laboratory diagnosis 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…The high sensitivity (94%) and specificity (100%) are similar to results reported in other studies. Ichiyama et al reported 97% sensitivity and 98.7% specificity, however Vuorinen et al reported slightly lower sensitivity of 84.6% and specificity of 99.1% using similar commercially available PCR (Amplicor) with IS6110 as a target site for laboratory diagnosis 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivities and specificities of these products have been reported to be similar, i.e., ranging from approximately 67 to 94% sensitivity and from 94 to 100% specificity. As has recently been noted, very few studies have provided a direct comparison of these two products (22,52). Evaluation of the published studies is therefore difficult given the wide range of protocols, reference methods, and study populations (19).…”
Section: Discussionmentioning
confidence: 99%
“…The PCR for the detec-tion of M. tuberculosis has been directed at both genomic DNA (46) and species-specific regions of 16S rRNA (Roche Amplicor) (13,14,34). Recently, several investigators have evaluated the Mycobacterium Tuberculosis Direct test (MTD; Gen-Probe, Inc., San Diego, Calif.), which couples transcriptionmediated amplification to Accuprobe detection technology (8,22,23,35). The U.S. Food and Drug Administration (FDA) has recently approved both Amplicor and MTD for testing of smear-positive specimens.…”
mentioning
confidence: 99%
“…The addition of nucleic acid amplification technology to the microbiology laboratories has resolved many of these problems. The exquisite sensitivity and specificity of these methods allow the accurate detection of very small number of microorganisms (Ichiyama et al, 1996and Jackson et al, 1996and Whelen et al, 1995. In selected situations, the limitation imposed by the inability of an organism to be cultured and the selection of appropriate media and culture conditions may be replaced by the use of nucleic acid amplification.…”
Section: Application Of Nucleic Acid Amplification Technologymentioning
confidence: 99%